2023
DOI: 10.1101/2023.03.06.531343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myosin VIII and XI isoforms interact withAgrobacteriumVirE2 protein and help direct transport from the plasma membrane to the perinuclear region during plant transformation

Abstract: Agrobacterium transfers T-DNA and effector proteins into plant cells. VirE2, one of these virulence effectors, enters the plant cell and is thought to bind T-strands. How VirE2 is trafficked inside the plant cell is not fully understood. Using bimolecular fluorescence complementation, in vitro pull-down, yeast two-hybrid, and in vivo co-immunoprecipitation assays, we found that VirE2 binds directly to the cargo binding domains of several myosin VIII family members, and to myosin XI-K. We observed reduced susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Although no obvious phenotype was initially observed in an Arabidopsis mutant lacking all four myosin VIIIs (Talts et al, 2016), a subsequent study reported a subtle phenotype for atm1 single knockouts, a reduced hypocotyl elongation that was recoverable by sucrose supplementation (Olatunji and Kelley, 2020). Recently, ATM1 was implicated in root apical meristem organization (Olatunji et al, 2022) and myosin VIIIs also appear to function in Agrobacterial transformation of Arabidopsis cells (Liu et al, 2023). The use of Physcomitrella patens as a model demonstrated that the loss of all five myosin VIIIs resulted in a pleiotropic phenotype that included reduced size and growth rate of gametophytes, suggesting roles in cell expansion and hormone homeostasis (Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no obvious phenotype was initially observed in an Arabidopsis mutant lacking all four myosin VIIIs (Talts et al, 2016), a subsequent study reported a subtle phenotype for atm1 single knockouts, a reduced hypocotyl elongation that was recoverable by sucrose supplementation (Olatunji and Kelley, 2020). Recently, ATM1 was implicated in root apical meristem organization (Olatunji et al, 2022) and myosin VIIIs also appear to function in Agrobacterial transformation of Arabidopsis cells (Liu et al, 2023). The use of Physcomitrella patens as a model demonstrated that the loss of all five myosin VIIIs resulted in a pleiotropic phenotype that included reduced size and growth rate of gametophytes, suggesting roles in cell expansion and hormone homeostasis (Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Myosin XIs are involved in a range of processes including endo and exocytosis, cytoplasmic streaming, nuclear shape and positioning, gravitropism, and biotic stress responses (Peremyslov et al, 2010;Tominaga and Nakano, 2012;Buchnik et al, 2015;Nebenführ and Dixit, 2018). In contrast, the roles of myosin VIIIs are not as well understood and a quadruple knockout of all four myosin VIII genes in Arabidopsis shows only subtle phenotypes (Talts et al, 2016;Liu et al, 2023). Nevertheless, studies on class VIII myosins have implicated them in plasmodesmatal function and endocytosis (Baluška et al, 2001;Golomb et al, 2008;Sattarzadeh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no obvious phenotype was initially observed in an Arabidopsis mutant lacking all four myosin VIIIs (Talts et al, 2016), a subsequent study reported a subtle phenotype for atm1 single knockouts, a reduced hypocotyl elongation that was recoverable by sucrose supplementation (Olatunji and Kelley, 2020). Recently, ATM1 was implicated in root apical meristem organization (Olatunji et al, 2022) and myosin VIIIs also appear to function in Agrobacterial transformation of Arabidopsis cells (Liu et al, 2023). The use of Physcomitrella patens as a model demonstrated that the loss of all five myosin VIIIs resulted in a pleiotropic phenotype that included reduced size and growth rate of gametophytes, suggesting roles in cell expansion and hormone homeostasis (Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Their enzymatic profile suggests tension sensor and/or tension generator activity rather than fast movement (Haraguchi et al, 2014;Henn and Sadot, 2014;Rula et al, 2018). In addition, recent reports show the involvement of myosin VIIIs in the movement of viral particles of tobacco mosaic, rice stripe, and rice grassy stunt viruses and the VirE2 protein from Agrobacterium tumefaciens (Pitzalis and Heinlein, 2017;Liu et al, 2023). In the moss Physcomitrella patens, myosin VIIIs function during cytokinesis (Wu and Bezanilla, 2014).…”
Section: Introductionmentioning
confidence: 99%